The Association between Alarm Fatigue, and Burnout among Nurses in Critical Care Units - Yousif, Sahar Yaqoob; AL-Fayyadh, Sadeq; Mottershead, Richard (Iraqi National Journal of Nursing Specialties, 2025)
Objective(s): To examine the association between alarm fatigue and burnout among nurses working in adult critical care units.Methods: A descriptive-correlational study design was used targeting 377 nurses practicing in critical care units within 13 hospitals in Iraq. Data gathering extended for the period from January 6th, 2024 to March 7th 2024, by investigating sociodemographic, professional characteristics of nurses, and alarm fatigue questionnaire, and the Burnout Assessment Tool.Results: Overall, 240 out of 377 nurses in critical care units showed a moderate degree of alarm fatigue, with a percentage of 63.7%. Of equal importance, the majority of nurses suffered from high levels of burnout, with a mean score of 2.53. The Pearson correlation (r =.441 at p = 0.01) also showed a positive association between alarm fatigue and burnout among nurses in critical care units.Conclusion: This study illuminated the statistically significant positive correlations between nurse’s alarm fatigue and each dimension of burnout (exhaustion, mental distance, cognitive impairment, emotional impairment, psychological complaints, psychosomatic complaints, secondary symptoms, and overall burnout).Recommendations: The provision of training sessions on stress management, building resilience strategies, and coping techniques provide nurses with the necessary tools to more effectively navigate the challenges of their profession. Furthermore, it is crucial to replicate this study in critical care units in other governorates of Iraq to compare and improve the generalization of the findings.